A Review on Applications of Superhydrophobic Materials in Civil Engineering. Issue 6 (5th December 2021) - Wang, Ning; Wang, Qing; Xu, Shuangshuang
Abstract : Superhydrophobic (SHPB) materials have attracted a lot of attention in civil engineering due to their unique wettability in recent years. The SHPB characteristics pave up a new way for the applications of SHPB materials in civil engineering. In this review, the applications research progress of SHPB materials in various fields of civil engineering is summarized. The waterproofing, self‐cleaning, anticorrosion, anti‐icing, and antifogging applications of SHPB materials in architectural engineering are discussed. The applications of SHPB materials in road and bridge engineering such as anti‐icing and antiskidding are listed. The applications of SHPB materials in heating and ventilation engineering are ranged from anticondensation, antifrosting to dust removal. The anticorrosion and antibiofouling applications of SHPB materials in structural engineering in marine environment are presented. The key problem of insufficient mechanical and chemical durability of SHPB materials when applied in civil engineering is pointed out, and the application trend of SHPB materials in civil engineering is prospected. Finally, based on the detailed discussion of the applications of SHPB materials in civil engineering, a brief summary is proposed. It is expected that SHPB materials can be widely and systematically applied in civil engineering, making important contributions to multifunctional development of civil engineering in the future. Abstract : Superhydrophobic (SHPB) materials have attracted a lot of attention in civil engineering due to their unique wettability in recent years. This article reviews the recent progress of application research on SHPB materials in various fields of civil engineering. It is expected that the SHPB materials may be widely and systematically applied in civil engineering.